Rise of first follow-up sodium in patients hospitalized with acute heart failure is associated with better outcomes. (15th October 2018) - Omar, Hesham R.; Guglin, Maya
Abstract: Introduction: The prognostic effect of the direction of change in sodium (Na) level from admission to subsequent check in patients with acute heart failure (HF) has not been previously explored. Methods: The ESCAPE trial data was utilized to study whether the rise of 1 st follow-up Na (at day 3) relative to admission (among patients with admission hyponatremia) is associated with favorable outcomes. The study endpoints were all-cause rehospitalization and a composite of death, rehospitalization and cardiac transplant, both up to 6-month after discharge. Results: Patients with rise of 1 st follow-up Na ( n  = 43) had an average admission Na of 130.1 meq/L which increased to 134 meq/L at day 3 ( P  < 0.001), while patients without rise of 1 st follow up Na ( n  = 46) had an admission Na of 131 meq/L which decreased to 128.9 meq/L at day 3 ( P  < 0.001). There was an inverse association between the magnitude of change in Na level from admission to day 3 and the magnitude of change in blood urea nitrogen (BUN, r  = −0.304, P  = 0.004), creatinine ( r  = −0.401, P  < 0.001) and weight ( r  = −0.279, P  = 0.011) during the same time frame. Among those 89 cases, 56 (63%) were rehospitalized and 70 (79%) experienced the composite endpoint. Patients without rise in 1 st follow-up Na had higher frequency of rehospitalization (76.1% vs. 48.8%, univariate Odds ratio (OR) 1.778, 95% CI 1.174–2.693, P  = 0.009) and composite endpoint (89.1% vs. 67.4%, univariate OR 1.779, 95% CI 1.208–2.619, P  = 0.017), compared with those with Na rise. Cox regression analysis showed that rise in 1 st follow-up Na was independently associated with reduced rehospitalization (Hazard ratio (HR) 0.429, 95% CI 0.191–0.960, P  = 0.04) and the composite endpoint (HR 0.430, 95% CI 0.201–0.920, P  = 0.03) after covariate adjustment. Conclusion: Rise of first follow-up Na in patients with HF decompensation and hyponatremia on admission is associated with favorable intermediate-term outcomes. Highlights: Admission hyponatremia in patients hospitalized with decompensated heart failure is dilutional. Discharge hyponatremia in patients with normal admission sodium is depletional. Rise of first follow-up Na in acute heart failure and admission hyponatremia is associated with favorable outcomes. The inverse association between magnitude of Na rise and body weight, BUN and creatinine, suggest that Na rise is a proxy for better decongestion.